The Effect of Green Credit and Other Determinants of Credit Risk Commercial Bank in Indonesia - Ressita Nugrahaeni; Harjum Muharam (Politeknik Siber Cerdika Internasional, 2023)
In order to achieve the Notionally Determined Contribution (NDC) target through reducing greenhouse gas emissions, the Government of Indonesia is trying to develop sustainable finance. Commercial Banks as a financial service institution are required to implement sustainable finance, among others by reporting loans that meet the criteria for Environmentally Friendly Business Activities (KUBL). Credit risk is one of the main risks for banks. Research on the effect of lending that meets KUBL or green loan criteria on bank credit risk as reflected in NPLs has never been carried out. In this study, we analyze the effect of green loans, and the influence of other variables, namely bank performance variables (LDR, CAR, ROA, NIM) and bank size on credit risk of commercial banks in Indonesia. This study uses annual available data from 107 commercial banks in Indonesia for the period from 2019 to 2021. Based on the results of this study, the effect of green loans on NPL is not significant because the percentage of green loans is relatively low compared to the total bank credit portfolio in Indonesia. For this reason, various incentives are needed from both the Authority and the Government to encourage commercial banks to increase green loans.Meanwhilebank performance variables, namely LDR, CAR, NIM and bank size have a significant influence on the credit risk of commercial banks in Indonesia. Bank performance variables namely LDR, CAR have a positive effect on bank NPLs, the NIM ratio and bank size have a negative effect on bank NPLs.